Sustainability Reporting and Corporate Performance: The Moderating Role of Corporate Internationalization - Yau, Josephine Tan-Hwang; Yu, Magdalene Sze-Ee; Amidjaya, Prihatnolo Gandhi; Liwan , Audrey; Kueh , Jerome Swee-Hui; Hamdan , Rosita (JAS (Journal of ASEAN Studies), 2024)
This study aims to investigate the relationship between sustainability reporting and corporate performance moderated by the internationalization level of the firms. The sample for this empirical study is collected from the Financial Times Stock Exchange (FTSE)100 firms listed on Bursa Malaysia for a period of nine years from 2011 to 2019. We examine the sustainability reporting based on the Global Reporting Initiative (GRI) standard with the G4 guideline, in which a content analysis method has been employed to obtain the Sustainability Reporting Index (SRI). The moderating variable for this study is the internationalization level, which is proxied by foreign sales generated. The findings demonstrate that sustainability reporting disclosure has no effect on corporate performance. However, internationalization improves corporate performance but serves no moderation role in the relationship between sustainability reporting and corporate performance. We conclude that there is no evidence to substantiate the claim that companies that disclose more in their sustainability reporting perform better, and this may be because Malaysian corporations are still new to non-financial reporting. We believe that although sustainability reporting is costly, sustainability reporting is able to enhance the reputation of firms in the international market. Sequentially, a highly internationalized firm with more sustainability reporting disclosures may bring wealth to the company in the long run.